(untitled) (Journal of Nematode Morphology and Systematics, 2012)
Bursaphelenchus macromucronatus sp. n. isolated in Ningbo, China, from Taiwanese and Indian packaging wood is described and illustrated. The new species has a body length of 761 (602-986) μm in females and 650 (510- 804) μm in males, robust body (a = 30 for females and 34 for males), stylet 13-14 μm long, excretory pore located at level of median bulb or slightly behind this, lateral fi eld with four lines, long post-uterine branch (average 101 μm) extending two-thirds to three-fourths of vulva-anus distance, female tail conical (c = 20) and slightly bent ventrally with a pointed terminal mucro 4.5(2.5-6.5) μm long, stout spicules (23-38 μm long) having a distinctly pointed rostrum and small cucullus, and a terminal bursa of variable shape, but often two-pointed. Its separation from other species of the xylophilus group is mainly based on female tail shape, spicules size and the mucro length. The new species can also be differentiated from B. xylophilus, B. mucronatus, B. fraudulentus, B. conicaudatus, B. luxuriosae, B. doui and B. singaporensis by means of ITS-RFLP and sequencing results.